Temporal profile and determinants of viral shedding and of viral clearance confirmation on nasopharyngeal swabs from SARS-CoV-2-positive subjects: a population-based prospective cohort study in Reggio Emilia, Italy - Mancuso, Pamela; Venturelli, Francesco; Vicentini, Massimo; Perilli, Cinzia; Larosa, Elisabetta; Bisaccia, Eufemia; Bedeschi, Emanuela; Zerbini, Alessandro; Giorgi Rossi, Paolo; Costantini, Massimo; Grilli, Roberto; Marino, Massimiliano; et al. (BMJ open, 2020)
ObjectivesTo determine the timing of viral clearance (first negative RT-PCR on nasopharyngeal swab) and the probability of viral clearance confirmation (two consecutive negative swabs) in COVID-19 patients and to identify related determinants.DesignPopulation-based prospective cohort study on archive data.SettingPreventive services and hospital care in the Reggio Emilia province, northern Italy.ParticipantsAll 1162 subjects testing positive to RT-PCR on nasopharyngeal swabs and diagnosed with COVID-19 in the Reggio Emilia province with at least 30 days of follow-up by 22 April 2020.Main outcome measuresMedian times from diagnosis and from symptom onset to viral clearance with IQR assessed using the Kaplan–Meier estimator, stratified by included characteristics. The probability of viral clearance confirmation, stratified by time from diagnosis and putative determinants assessed using a multivariate logistic regression model.ResultsViral clearance was achieved by 60.6% (704/1162) of patients, with a median time of 30 days from diagnosis (IQR 23–40) and 36 days from symptom onset (IQR 28–45). Of those negative and retested, 78.7% (436/554) had viral clearance confirmation, suggesting one in five false negative tests. The time from symptom onset to viral clearance slightly increased with age, from 35 (IQR 26–44) days under age 50 to 38 (IQR 28–44) in over age 80, and with disease severity, from 33 (IQR 25–41) days in non-hospitalised subjects to 38 (IQR 30–47) days in hospitalised patients. The probability of confirmed viral clearance reached 86.8% after 34 days from symptom onset and increased with time, even when adjusting for age and sex (OR 1.16 95% CI 1.06 to 1.26 per day from diagnosis).ConclusionsPostponing follow-up testing of clinically recovered COVID-19 patients could increase the efficiency and performance of testing protocols. Understanding viral shedding duration also has implications for containment measures of paucisymptomatic subjects.